Evaluasi Pembelajaran Nilai-Nilai Aneka dan Pengaruhnya Terhadap Perilaku Alumni Latsar CPNS - Burdan Ali Junjunan (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The State Civil Apparatus (ASN) must be able to actualize the five basic values of ASN which consist of Accountability, Nationalism, Public Ethics, Quality Commitment and Anti-Corruption (ANEKA) based on Law Number 5 of 2014 concerning ASN. These basic values of ANEKA are the initial capital for ASN in carrying out its main duties and functions in the working institution. This study aims to determine the effect of understanding the basic values of ANEKA on behaviour change before and after basic training (Latsar) CPNS. This research uses mixed methods research. In the quantitative stage, data from 162 CPNS Class 1 to 12 the Year 2019 Latsar participants collected through a questionnaire survey were analyzed using the Paired Samples t-Test method technique, while the qualitative stage was conducted by conducting an interview process and open questionnaires to 162 CPNS Class 1 to 12 of 2019 and 8 supervisors of the work unit of the Latsar participants were analyzed descriptively. The results showed that there was an effect of the basic values of Accountability (X1), Nationalism (X2), Public Ethics (X3), Quality Commitment (X4) and Anti-Corruption (X5) in before and after attending CPNS Latsar on behaviour changes in Latsar participants. CPNS so that according to the supervisor of the work unit there was a significant change in the behaviour of the participants by the expected behaviour as a professional CPNS compared to before being included in the CPNS Latsar and there were obstacles experienced by the CPNS Latsar participants having difficulty actualizing ANEKA's basic values in the form of work behaviour.